Molecular Imaging of Valvular Diseases and Cardiac Device Infection. (17th January 2023) - Tarkin, Jason M.; Chen, Wengen; Dweck, Marc R.; Dilsizian, Vasken
Abstract : The use of positron emission tomography imaging with 18 F-fluorodeoxyglucose in the diagnostic workup of patients with suspected prosthetic valve endocarditis and cardiac device infection (implantable electronic device and left ventricular assist device) is gaining momentum in clinical practice. However, in the absence of prospective randomized trials, guideline recommendations about 18 F-fluorodeoxyglucose positron emission tomography in this setting are currently largely based on expert opinion. Measurement of aortic valve microcalcification occurring as a healing response to valvular inflammation using 18 F-sodium fluoride positron emission tomography represents another promising clinical approach, which is associated with both the risk of native valve stenosis progression and bioprosthetic valve degeneration in research trials. In this review, we consider the role of molecular imaging in cardiac valvular diseases, including aortic stenosis and valvular endocarditis, as well as cardiac device infections.